Pengaruh pemberian edukasi kepada pengasuh terhadap tingkat kepatuhan pemberian obat anti epilepsi pada anak dengan epilepsi - I Gusti Ngurah Made Suwarba; Ni Made Dani Febriansiswanti; Anita Purnamayanti (DiscoverSys Inc., 2021)
Background: Adherence was the main problem in anti-epilepsy drug therapy because it has to be consumed up to 2 years free of seizures to require education intervention. This research aimed to analyze the effect of oral and written (leaflet) education on patient carer's adherence level in administering epilepsy medicines to the pediatric patient (?18 years old).Methods: The design of This study was one group pre - post-test research. Subjects were collected using consecutive sampling.Results: This study's subject was 24 patient carers with low and moderate levels of medication adherence. Oral and written education material was provided every week for eight weeks, and the adherence level was analyzed through the pills count and self-report checklist every week during the study. The Wilcoxon signed-rank test results were significantly different between pre and post-pill counts, and the result of repeated measure test showed that there was an increasing level of medication adherence significantly in third obtained by pill count method week ( p=0,000 ) and remained high until the end of this study.Conclusion: Oral and written education could improve the caregivers administering medication adherence level to their epilepsy children. Latar belakang: Kepatuhan merupakan masalah utama dalam terapi obat anti epilepsi karena obat anti epilepsi harus dikonsumsi sampai 2 tahun bebas kejang, sehingga diperlukan edukasi. Penelitian ini bertujuan untuk menganalisis pengaruh pemberian edukasi berupa lisan dan tertulis (leaflet) terhadap tingkat kepatuhan pemberian obat oleh pengasuh kepada pasien epilepsi anak usia ?18 tahun.Metode: Rancangan penelitian ini adalah one group pre – post test design. Pengumpulan subjek dengan consecutive sampling.Hasil: Subjek penelitian sebanyak 24 orang dengan kriteria tingkat kepatuhan rendah dan sedang. Edukasi lisan dan tertulis diberikan setiap minggu selama 8 minggu, penilaian tingkat kepatuhan melalui pill count dan self report checklist setiap minggu selama 8 minggu. Hasil uji wilcoxon signed rank terdapat perbedaan pre pill count dan post pill count, dan hasil uji repeated measure terdapat pengaruh pemberian edukasi, yang dapat dilihat dari peningkatan nilai pill count secara signifikan pada minggu ke-3 (p=0,000) dan tetap tinggi sampai akhir penelitian.Simpulan: Pemberian edukasi berupa lisan dan tertulis memberikan pengaruh peningkatan kepatuhan pemberian obat oleh pengasuh kepada pasien epilepsi anak.